Ensembl Genomes 2020—enabling non-vertebrate genomic research. Issue Volume 48:Issue D1(2020) (10th October 2019) - Howe, Kevin L; Contreras-Moreira, Bruno; De Silva, Nishadi; Maslen, Gareth; Akanni, Wasiu; Allen, James; Alvarez-Jarreta, Jorge; Barba, Matthieu; Bolser, Dan M; Cambell, Lahcen; Carbajo, Manuel; Chakiachvili, Marc; et al.
Abstract: Ensembl Genomes (http://www.ensemblgenomes.org ) is an integrating resource for genome-scale data from non-vertebrate species, complementing the resources for vertebrate genomics developed in the context of the Ensembl project (http://www.ensembl.org ). Together, the two resources provide a consistent set of interfaces to genomic data across the tree of life, including reference genome sequence, gene models, transcriptional data, genetic variation and comparative analysis. Data may be accessed via our website, online tools platform and programmatic interfaces, with updates made four times per year (in synchrony with Ensembl). Here, we provide an overview of Ensembl Genomes, with a focus on recent developments. These include the continued growth, more robust and reproducible sets of orthologues and paralogues, and enriched views of gene expression and gene function in plants. Finally, we report on our continued deeper integration with the Ensembl project, which forms a key part of our future strategy for dealing with the increasing quantity of available genome-scale data across the tree of life.